PENGARUH KINERJA BELAJAR PADA MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP HASIL BELAJAR - Citra Mutiara; Eko Suyanto; Abdurrahman Abdurrahman (Jurnal Pembelajaran Fisika, 2014)
Some of students did not have performance yet to comprehend physics problem that had been given by the teacher. The research's objective is to recognize the influence of learning performance toward student's learning result through instructional model of creative problem solving (cps) . The population of the research was all of the first grade students in MAN 1 Bandar Lampung, second semester of academic year 2012/2013. The sample was class X 5, which was taken by random sampling method. The design of this research was one group pretest-posttest. The result of research showed that there was positive and significant effect of study performance toward student's learning result through instructional model of creative problem solving (cps).Sebagian siswa belum memiliki kinerja yang dimiliki untuk memahami masalah Fisika yang diberikan guru. Tujuan penelitian untuk mengetahui pengaruh kinerja belajar siswa terhadap hasil belajar pada model pembelajaran creative problem solving. Populasi penelitian seluruh siswa kelas X MAN 1 Bandar Lampung semester genap tahun ajaran 2012/2013. Pengambilan sampel menggunakan random sampling, kelas X 5. Penelitian menggunakan desain one group pretest-postest. Hasil penelitian terdapat pengaruh positif dan signifikan kinerja belajar terhadap hasil belajar melalui model pembelajaran crative problem solving.Kata kunci: hasil belajar, kinerja belajar, model pembelajaran CPS.